Membangun Lemma Ekonomi Islam Berbasis QawÃ¢âid al-Fiqhiyah (Studi Kasus Ø§ÙØ¶Ø±Ø± ÙØ²Ø§Ù ) - Sugianto, Sugianto (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2014)
Lemma is a statement that can be accepted as a theoretical assumptions derived from axioms. A theory is formed as a reflection of reality and proportion of the lemma is sourced from the axiom that the level of its truth comes from revelation. This paper aims to explore qawÃ¢id al-fiqhiyah, including al-dhararu yuzÃ¢l, as a statement from the ultimate source of truth, revelation (al-Quran and Hadith) as a lemma to build Axioma in economic studies. This axiom then is made as basic arguments in the compilation of Islamic economic theory.